PENGARUH SISA LEBIH PERHITUNGAN ANGGARAN DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH: ANALISIS PERUBAHAN APBD KABUPATEN/KOTA SE-ACEH - Martunis Martunis; Darwanis Darwanis; Syukriy Abdullah (Program Magister Akuntansi Unsyiah, 2014)
This study aimed to examine the effect of Time over Budget Calculation (SiLPA) and Local Revenue (PAD) on local expenditure in Aceh. The population in this study is LKPD districts/cities in Aceh, amounting to 23 districts/cities consist of 18 counties and 5 cities. While the unit of analysis is the study of purely budgetary data and changing budget allocations data for the period 2009-2012 changes in 23 districts/cities in Aceh. Data analysis techniques in this study using multiple linear regression analysis. This study shows that SiLPA and PAD either jointly or separately affect the local expenditure districts/cities in Aceh. Keywords:Time over Budget Calculation (SiLPA), Local Revenue (PAD), Local Expenditure